PEDOT:PSS hydrogels with high conductivity and biocompatibility for in situ cell sensing. Issue 14 (24th March 2023) - Yang, Taotao; Yang, Ming; Xu, Chao; Yang, Kun; Su, Yuming; Ye, Yongqin; Dou, Lingyun; Yang, Qin; Ke, Wenbo; Wang, Bin; Luo, Zhiqiang
Abstract : Highly conductive and biocompatible PEDOT:PSS hydrogels, prepared by using conductive polymers as cross-linkers, can serve as both an electrochemical sensor and as a 3D hydrogel scaffold to realize in situ sensing of DA secreted by PC12 cells. Abstract : Conducting polymer hydrogels, especially poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) hydrogels, show great promise in soft bioelectronics due to their high conductivity and the ability of electrical coupling with tissues for sensing and stimulation. However, it is challenging to solve the problem of poor biocompatibility of PEDOT:PSS hydrogels due to the existing harsh preparation methods with the use of toxic and harmful reagents. Herein, we report the synthesis of PEDOT:PSS hydrogels with positively charged conductive polymers as a cross-linker and the application of PEDOT:PSS hydrogels as in situ electrochemical sensors for living cells. The conductivities of PEDOT:PSS hydrogels prepared using this method without any toxic or harmful reagents can reach up to 3265 S m −1 . The facile synthesis approach with a simple mixture of PEDOT:PSS aqueous solution and the monomers of conductive polymers at room temperature also enables the printability of PEDOT:PSS hydrogels to fabricate patterned electrodes. Moreover, all the proposed PEDOT:PSS hydrogels demonstrated good biocompatibility. The in situ electrochemical detection of dopamine secreted from PC12 cells cultured within PEDOT:PSS hydrogels suggests that our PEDOT:PSS hydrogels with high conductivity and biocompatibility offer great potential for the integration of biosensors within 3D cell culture.